Search for QCD instanton-induced processes at HERA in the high-Q2 domain - Andreev, Vladimir; Bolz, Arthur; Huber, Florian; Sauter, Michel David; Schöning, André (The European physical journal. C, Particles and fields, 2016)
Signals of QCD instanton-induced processes are searched for in neutral current deep-inelastic scattering at the electron-proton collider HERA in the kinematic region defined by the Bjorken-scaling variable > 10^{-3}$$x>10-3, the inelasticity $$0.2< y < 0.7$$0.2<y<0.7and the photon virtuality $$150< Q^2 < 15000$$150<Q2<15000 GeV$$^2$$2. The search is performed using H1 data corresponding to an integrated luminosity of 351 pb$$^{-1}$$-1. No evidence for the production of QCD instanton-induced events is observed. Upper limits on the cross section for instanton-induced processes between 1.5 and 6 pb, at $$95\,\,%$$95% confidence level, are obtained depending on the kinematic domain in which instantons could be produced. Compared to earlier publications, the limits are improved by an order of magnitude and for the first time are challenging predictions.
Im Titel ist die Zahl "2" hochgestellt
H1 Collaboration: V. Andreev, A. Baghdasaryan, K. Begzsuren, A. Belousov, A. Bolz, V. Boudry, G. Brandt, V. Brisson, D. Britzger, A. Buniatyan, A. Bylinkin, L. Bystritskaya, A.J. Campbell, K.B. Cantun Avila, K. Cerny, V. Chekelian, J.G. Contreras, J. Cvach, J.B. Dainton, K. Daum, C. Diaconu, M. Dobre, V. Dodonov, G. Eckerlin, S. Egli, E. Elsen, L. Favart, A. Fedotov, J. Feltesse, J. Ferencei, M. Fleischer, A. Fomenko, E. Gabathuler, J. Gayler, S. Ghazaryan, L. Goerlich, N. Gogitidze, M. Gouzevitch, C. Grab, A. Grebenyuk, T. Greenshaw, G. Grindhammer, D. Haidt, R.C.W. Henderson, J. Hladkỳ, D. Hoffmann, R. Horisberger, T. Hreus, F. Huber, M. Jacquet, X. Janssen, H. Jung, M. Kapichine, J. Katzy, C. Kiesling, M. Klein, C. Kleinwort, R. Kogler, P. Kostka, J. Kretzschmar, D. Krücker, K. Krüger, M. P.J. Landon, W. Lange, P. Laycock, A. Lebedev, S. Levonian, K. Lipka, B. List, J. List, B. Lobodzinski, E. Malinovski, H.-U. Martyn, S.J. Maxfield, A. Mehta, A.B. Meyer, H. Meyer, J. Meyer, S. Mikocki, A. Morozov, K. Müller, Th. Naumann, P.R. Newman, C. Niebuhr, G. Nowak, J.E. Olsson, D. Ozerov, C. Pascaud, G.D. Patel, E. Perez, A. Petrukhin, I. Picuric, H. Pirumov, D. Pitzl, R. Plačakytė, B. Pokorny, R. Polifka, V. Radescu, N. Raicevic, T. Ravdandorj, P. Reimer, E. Rizvi, P. Robmann, R. Roosen, A. Rostovtsev, M. Rotaru, S. Rusakov, D. Šálek, D.P.C. Sankey, M. Sauter, E. Sauvan, S. Schmitt, L. Schoeffel, A. Schöning, F. Sefkow, S. Shushkevich, Y. Soloviev, P. Sopicki, D. South, V. Spaskov, A. Specka, M. Steder, B. Stella, U. Straumann, T. Sykora, P.D. Thompson, D. Traynor, P. Truöl, I. Tsakov, B. Tseepeldorj, J. Turnau, A. Valkárová, C. Vallée, P. Van Mechelen, Y. Vazdik, D. Wegener, E. Wünsch, J. Žáček, Z. Zhang, R. Žlebčík, H. Zohrabyan, F. Zomer
Gesehen am 18.08.2020